Effect of Humic Acid and Phosphate Fertilizer on Carbon Biomass of Microorganisms at the Corn Plantation Field in Ultisol Soil - Fauzan Ag. Roni; Sri Yusnaini; M.A. Syamsul Arif; Ainin Niswati (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2026)
Ultisol soils are soils with low fertility levels which are characterized by high soil acidity (low pH), low cation exchange capacity and base saturation levels, and low nutrient content such as the availability of P nutrients. In order to improve the soil fertility by applying  organic matter such as humic acid. The objectives of this study were to studies: (1) the effect of the best application of humic acid on soil microbial carbon biomass (C-mic) in maize cultivation on Ultisol soils; (2) the effect of the best phosphate fertilization level on soil microorganism carbon biomass (C-mic) in maize cultivation on Ultisol soil; (3) the effect of interaction between humic acid and phosphate fertilization on soil microorganism carbon biomass (C-mic) in maize cultivation in Ultisol soils; and (4) whether there is a correlation between soil organic C, soil moisture content, soil pH, and soil temperature with soil microorganism carbon biomass (C-mic) in maize cultivation in Ultisol soils. This study was arranged in a randomized block design with Humic acid application treatment of 0 kg ha-1 (H0), 5 kg ha-1 (H1), and 10 kg ha-1 (H2) combined to phospahte application with level of 0 kg ha-1 (P0); 100 kg ha-1 (P1), 200 kg ha-1 (P2), and 300 kg ha-1 (P3). The average value of C-mic biomass, C-organic content, soil pH, soil moisture content, soil temperature, and corn production were tested with orthogonal polynomials at significant levels of 5 and 1%. The results showed that: (1) application of humic acid was not increase soil microorganism carbon biomass (C-mic) in maize cultivation on Ultisol soils; (2) the application of phosphate fertilizer (P) did not increase soil C-mic biomass in maize cultivation on Ultisol soils; (3) there is an interaction between humic acid and phosphate (P) fertilization on soil C-mic biomass in maize cultivation on Ultisol soil. The application of humic acid at a dose of 5 kg ha-1 (H1) combined with phosphate fertilization of 174.83 kg ha-1 resulted in a maximum C-mic biomass of 32.25 mg C-CO2 kg-1 day-1. The application of phosphate fertilizer along with humic acid application of 10 kg ha-1 (H2) caused a linear increase in C-mic biomass at 90-day after planting (DAP), the higher the application of phosphate up to 300 kg ha-1 the formation of C-mic biomass still continued to increase; and (4) there is no correlation between soil organic C, soil moisture content, and soil temperature on C-mic biomass, but there is a correlation between C-mic biomass and the reaction (pH) of soil in maize cultivation in Ultisol soils. Keywords:  Humic acid, soil microbial carbon biomass (C-mic), ultisol soils